Bukit Choras Archaeological Complex: Geophysical And Geo-Archaeological Analysis - Dishong, Nini Havela (2022)
Ancient Kedah is a collection of several riverine and coastal settlements which flourished as the foci for international trade and industry between the 2nd to the 14th Century C.E. The Bukit Choras Archaeological Complex is one of the very few well-preserved archaeological findings related to the cultural and economic development of Ancient Kedah. Previous studies had revealed two structural remains made of laterite bricks, two ancient water tanks, as well as other artefacts such as potsherds, Buddhist inscription and corroded iron nails. This research attempts to answer questions regarding the layout, building material and palaeo-environment of the site. In this study, geophysical studies were carried out in Bukit Choras in order to map the surface remains and to determine the potential for buried remains. Detailed contour mapping as well as the magnetic, resistivity and ground penetrating radar methods were done around the main structure and the ancient water tank.